Globalización, propiedad intelectual y políticas públicas en América Latina - Delich, Valentina (SocietàMutamentoPolitica, 2018)
The article explores the challenges posed by the dynamics of international intellectual property rights’ rules and institutions over Latin American democracies. As new knowledge emerges as the center piece of the global economy, disputes over the rules determining its ownership become bitter but crucial.